Sex on Show: 21 Hot Erotic Short Stories - Stigsdotter, Saga (Saga Egmont, 2023)
\'Sex on 21 Hot Erotic Short Stories\' is a collection from LUST that explore the sexy and sensual side of performances and shows. From public displays of affection and peep shows to dancers and rock stars, there\'s a steamy story for every reader..